La presencia de modelos cántabros en la arquitectura montañesa de León. La casa palacio de los Gómez de Caso en Burón - Campos Sánchez-Bordona, María Dolores (Estudios humanísticos. Geografía, historia y arte, 1994)
The investigation is based in the palace of the noble family Gomez de Caso, situated in the village of Burón (león). This building is a good example of the lordly architecture at the begining of the XVII century in the nort artea of Leon’s mountains, in which it, appears big influences of the tradicional architecture of Cantabria and Asturias.